Selected aspects of ideological content in the decoration of the Chapel of St. Francis Xavier at the Church of the Most Sacred Name of Jesus in Wrocław - Małgorzata Wyrzykowska (Quart, 2024)
The university church, together with the Collegium Maximum, was the most important foundation of the Wrocław Jesuits, which was reflected in the rich ideological programme of the decoration of this building complex. The aim of this article is to analyse selected aspects of the ideological content contained in the decoration of the chapel of St. Francis Xavier in the Church of the Most Sacred Name of Jesus in Wrocław, which has not yet received a monographic study. The literature on the subject emphasises how much attention the Jesuits paid to the message inscribed in the decoration of their buildings, and how they used the power of art to this end. Within this context, religious and political themes have been read and their authors identified. The source material for the analysis of the content of the chapel’s decoration consisted of fragmentary preserved Jesuitica, including Litterae annuae and an inventory of the Jesuit library in Wrocław from 1707. Indirect evidence suggests that the ideological programme and artistic expression of this interior was heavily influenced by the college rector Friedrich Wolff von Lüdinghausen (1643–1708) and prince bishop Franz Ludwig von Pfalz-Neuburg (1664–1732). The article also identifies the formal patterns of these ornaments.